2018
DOI: 10.1109/lsens.2017.2778248
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electrochemical Impedance of a Continuous Glucose Monitoring Sensor and its Correlation With Sensor Performance

Abstract: Abstract-In this work, we study the change in the sensitivity and the electrochemical impedance of continuous glucose monitoring sensors over time. 28-day sensitivity and EIS measurement results on four similar sensors are presented. The sensitivity of the sensor is observed to be related to its double-layer capacitance and charge-transfer resistance, based on results acquired from a sensor that showed substantial sensitivity drop. Two data clusters are extracted that relate the sensor sensitivity to its imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The authors have studied the electrochemical impedance and the sensitivity of commercially available CGM sensors (Medtronic Enlite sensors; working electrode area of 2 mm2) over the life-time of the sensors. The results presented in [10] show that the sensitivity is related to the double-layer capacitance and charge-transfer resistance, based on results acquired from a sensor that showed substantial sensitivity drop. Two data clusters are extracted that relate the sensor sensitivity to its impedance before and after the sensitivity drops by more than 50% (see Fig.…”
Section: A Sensor Calibrationmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors have studied the electrochemical impedance and the sensitivity of commercially available CGM sensors (Medtronic Enlite sensors; working electrode area of 2 mm2) over the life-time of the sensors. The results presented in [10] show that the sensitivity is related to the double-layer capacitance and charge-transfer resistance, based on results acquired from a sensor that showed substantial sensitivity drop. Two data clusters are extracted that relate the sensor sensitivity to its impedance before and after the sensitivity drops by more than 50% (see Fig.…”
Section: A Sensor Calibrationmentioning
confidence: 89%
“…The correlation between sensor sensitivity and double layer capacitance: two data clusters are visible around the initial and reduced sensitivity of the sensor. Reprinted from [10] indication of the end of the life-time of the sensor. This feature can be embedded into the wearable device to check the health of the sensor and to implement real-time calibration based on impedance; eliminating the need for external gold references for sensor calibration.…”
Section: A Sensor Calibrationmentioning
confidence: 99%
“…It is also imperative to study the biofouling effects from the sample and how calibrations may be carried out conveniently. For instance, [93] demonstrated that there is a correlation between the occurrence of a fault in the glucose sensor with the sensor's double-layer capacitance. Such a correlation introduces the possibility for an in-situ faulty sensor detection or potentially sensor calibration, where sensor sensitivity may be predicted in situ through easily measurable sensor characteristics such as impedance.…”
Section: B1 Sensor Reusability and Calibrationmentioning
confidence: 99%
“…Redox-mediated glucose biosensor faced problems in maintaining mediator and enzyme near the electrode due to small and diffusive molecules [11].The third generation enzymatic electrochemical biosensors do not require mediator where electrons are directly transferred between enzymes and electrodes [11]. Recent advances in nanostructures and nanotubes such as graphene and carbon nanotubes are promising for the development of nano electrodes and enzymatic electrochemical nano sensors used to develop convenient blood glucose monitors [12][13][14]. Enzymatic electrochemical biosensors are characterized by shorter stability; relatively higher fabrication costs, complicated modification and limitations associated with the nature of enzymes such as irreversibility, and signal drift [6,15,16].…”
Section: Invasive Blood Glucose Monitoring Techniques 21enzymatic Electrochemical Sensingmentioning
confidence: 99%